A novel dermoscopic feature in traumatic onycholysis - Ahu Yorulmaz (Our Dermatology Online, 2018)
Dermoscopy has certainly had a profound impact on the clinical diagnosis and management of both pigmented and nonpigmented skin lesions. Over the years, there has been much emphasis on the use of dermoscopy for the diagnosis of onychopathies. Traumatic onycholysis has been considered as one of the most common onychopathies. Although history and clinical examination remain the most crucial steps, dermoscopy apppears to be a rapid and effective tool in establishing the diagnosis of traumatic onycholysis. Here, we present two cases of traumatic onycholysis with classical and novel dermoscopic findings.